2017
DOI: 10.1186/s40795-017-0176-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of complementary feeding practices in South Asian infants and young children: the Bangladesh perspective

Abstract: Background: Sub-optimal nutrition among children remains a problem across South Asia (SA). Appropriate complementary feeding practices (CFP) can greatly reduce this risk. The primary objective of this systematic review (SR) of CF studies was to assess timing, dietary diversity, meal frequency and influencing factors in children under two in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 35 publications
(162 reference statements)
1
42
2
Order By: Relevance
“…Other papers published by our group as part of this project reviewed CF practices in Bangladesh, Pakistan, and India [ 16 , 17 , 18 ]. As reported in this review, the most common CF food groups for SA infants in high-income countries were “fruits and vegetables”, “flesh foods” and “dairy products”, described by six studies each, whereas the other reviews found “Grains, roots and tubers” were most commonly used for CF in the SA countries themselves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other papers published by our group as part of this project reviewed CF practices in Bangladesh, Pakistan, and India [ 16 , 17 , 18 ]. As reported in this review, the most common CF food groups for SA infants in high-income countries were “fruits and vegetables”, “flesh foods” and “dairy products”, described by six studies each, whereas the other reviews found “Grains, roots and tubers” were most commonly used for CF in the SA countries themselves.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in this review, the most common CF food groups for SA infants in high-income countries were “fruits and vegetables”, “flesh foods” and “dairy products”, described by six studies each, whereas the other reviews found “Grains, roots and tubers” were most commonly used for CF in the SA countries themselves. For example, “Grains, roots and tubers” were reported by 26 of 27 studies investigating dietary diversity in Bangladesh [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review of complementary feeding practices in South Asian Infants identified low education and ill-understood policies in infant and young child feeding (at community level) among the top barriers to appropriate complementary feeding practices [34]. A publication of data from 5 individual South Asian countries also reported a lack of maternal education and lower household wealth as the most consistent determinants of inappropriate practices in complementary feeding [35].…”
Section: Temperamental Characteristics and Regulatory Capacitiesmentioning
confidence: 99%